FORECASTING OF THE ROUTE NETWORK OF FERRY AND CRUISE LINES BASED ON SIMULATION AND INTELLIGENT TRANSPORT SYSTEMS - Nikolai MAIOROV; Vladimir FETISOV; Srećko KRILE; Darijo MISKOVIC (Transport Problems, 2019)
According to statistics, the marine passenger transportation sectors (both cruise lines and ferry lines) show a significant increase of passenger traffic and the intensity of ship routes. But new features of the conditions for passenger traffic growth require the development of new methodological transport models for cruise and ferry networks and new practical forecasting methods. Changes are observed in the fleet composition, mostly in the direction of increased. New approach for forecasting has to be based on the interaction of such systems as «city‒sea passenger port‒cruise and ferry lines». This condition now determines new need to describe the principles and forms of organization of maritime ferry networks and changes under the influence of the external environment. The object of the research is the Baltic Sea region and the existing route networks of cruise and ferry lines. Exploring this system, the usage of new mathematical apparatus based on correspondence matrices and agent-based simulation was justified for estimating the workload on transport infrastructure around the passenger port and for the existing ferry or cruise route network. The practical results of new simulation model, on the one hand, justify the need for a comprehensive study of the conditions for the formation of ferry and cruise route networks in changing conditions. On the other hand, these new results could improve the quality of decision-making process in forecasting the route network on the basis of the research of passenger traffic between systems «city‒sea terminal‒cruise line or ferry line».